B Cells and Progressive Multifocal Leukoencephalopathy: Search for the Missing Link - Durali, Deniz; de Goër de Herve, Marie-Ghislaine; Gasnault, Jacques; Taoufik, Yassine (Frontiers in Immunology, 2015)
Progressive multifocal leukoencephalopathy (PML) is a deadly demyelinating disease due to JC virus (JCV) replication in the brain. PML classically occurs in patients with severe immunodepression, and cases have recently been linked to therapeutic monoclonal antibodies such as natalizumab and also rituximab, which depletes B cells. B cells appear to play a complex role in the pathogenesis of PML. They may act as a viral reservoir and as a vector for viral dissemination in the CNS. Anti-JCV antibody responses appear to have a limited effect on JCV replication in the brain. However, accumulating evidence suggests that B cells may considerably influence T cell responses through their cytokine secretion. This immunomodulatory function of B cells may play an important role in the control of JCV infection and in the pathogenesis of PML, including rituximab-induced PML.